2017
DOI: 10.3389/fnsys.2017.00013
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Receptive Field Dynamics in Area V4 at the Time of Eye Movements?

Abstract: How we perceive the world as stable despite the frequent disruptions of the retinal image caused by eye movements is one of the fundamental questions in sensory neuroscience. Seemingly convergent evidence points towards a mechanism which dynamically updates representations of visual space in anticipation of a movement (Wurtz, 2008). In particular, receptive fields (RFs) of neurons, predominantly within oculomotor and attention related brain structures (Duhamel et al., 1992; Walker et al., 1995; Umeno and Goldb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 20 publications
15
49
1
Order By: Relevance
“…Our results are consistent with recent neurophysiological evidence [19], [20] that these two mechanisms have a different time course, with enhancement of the saccade target happening earlier (Experiment 1B) and maximum changes in spatial tuning (spatial compression) happening closer to saccade onset (Experiments 3B and 4). …”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with recent neurophysiological evidence [19], [20] that these two mechanisms have a different time course, with enhancement of the saccade target happening earlier (Experiment 1B) and maximum changes in spatial tuning (spatial compression) happening closer to saccade onset (Experiments 3B and 4). …”
Section: Discussionsupporting
confidence: 93%
“…This indicates that forward remapping, like any other attentional process, requires some time. As we observed three separate focuses of attention (at the saccade target, cue and remapped location), we definitely ruled out the hypothesis that during saccade preparation attention spreads around the saccade target, as expected by the convergent remapping hypothesis 15,23,24 .…”
Section: Discussionsupporting
confidence: 52%
“…A more recent work indicated that the visual system may, in fact, implement both forward and convergent remapping of receptive fields in area V4 16,30 . As this combined approach has been criticized on technical grounds 23 , the neurophysiological results regarding the existence of forward remapping remain inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive remapping has been observed in many other areas: in extrastriate visual cortex (Nakamura & Colby, 2002), SC (Walker, Fitzgibbon, & Goldberg, 1995) and FEF (Umeno & Goldberg, 1997;Sommer & Wurtz, 2006). However, in these early studies predictive remapping was not clearly delineated from other receptive field shifts as discussed by Zirnsak, Lappe, and Hamker (2010) which triggered new experimental observations (Zirnsak, Steinmetz, Noudoost, Xu, & Moore, 2014;Neupane, Guitton, & Pack, 2016a, 2016bHartmann, Zirnsak, Marquis, Hamker, & Moore, 2017). This report focuses on modeling the neural substrates of the original predictive remapping phenomenon, as described by Duhamel et al (1992).…”
Section: Predictive Remappingmentioning
confidence: 97%